2017
DOI: 10.1038/s41598-017-08669-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanopriming technology for enhancing germination and starch metabolism of aged rice seeds using phytosynthesized silver nanoparticles

Abstract: Application of nanomaterials for agriculture is relatively new as compared to their use in biomedical and industrial sectors. In order to promote sustainable nanoagriculture, biocompatible silver nanoparticles (AgNPs) have been synthesized through green route using kaffir lime leaf extract for use as nanopriming agent for enhancing seed germination of rice aged seeds. Results of various characterization techniques showed the successful formation of AgNPs which were capped with phytochemicals present in the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
252
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 501 publications
(297 citation statements)
references
References 100 publications
9
252
2
1
Order By: Relevance
“…In comparative phytotoxicity studies, our group has demonstrated the negative impacts of bulk Fe particles as compared to the Fe nanoparticles on chlorophyll synthesis of watermelon seedlings 11 . Our results are in agreement with similar studies by other groups, which have demonstrated the inhibitory effect of bulk silver particles as compared to silver nanoparticles 26,35,36 . These studies confirmed the phytotoxic effects of silver are not due to nanoparticles but owing to the Ag + ions.…”
Section: Scientific Reports |supporting
confidence: 94%
See 3 more Smart Citations
“…In comparative phytotoxicity studies, our group has demonstrated the negative impacts of bulk Fe particles as compared to the Fe nanoparticles on chlorophyll synthesis of watermelon seedlings 11 . Our results are in agreement with similar studies by other groups, which have demonstrated the inhibitory effect of bulk silver particles as compared to silver nanoparticles 26,35,36 . These studies confirmed the phytotoxic effects of silver are not due to nanoparticles but owing to the Ag + ions.…”
Section: Scientific Reports |supporting
confidence: 94%
“…Significant differences in yield were also observed in AgNP-treated watermelon of both cultivars at Snook, as well as non-significant increases in Grapeland and Weslaco. The results are in agreement with studies on onion 41 , Brassica juncea 33 , common beans, corn 42 , safflower cultivars 43 , rice 26 , and wheat 44 . AgNPs increased plant growth and biochemical attributes of Brassica juncea 33 , and seed yield of safflower cultivars 43 .…”
Section: Scientific Reports |supporting
confidence: 91%
See 2 more Smart Citations
“…Different priming techniques have been applied in agriculture crops to alleviate seed dormancy, improve germination rates, enhance seedling vigor and seedling capacity to grow and establish across a range of sites with varying environmental conditions [13][14][15][16][17][18][19]. Such priming techniques include hydrating seeds in salt solutions (halopriming), solutions of beneficial microbes (biopriming), osmotic solution (osmopriming), plant hormones solutions (hormonal priming), presence of a magnetic field (magneto-priming), solutions mixed with a solid carrier (matriconditioning), solutions of nanoparticles (nanopriming) or hydrating seeds in water (hydropriming) [15,20,21]. The realization of the potential use of nanotechnology in many sectors, including agriculture, has increased recently [18,22,23].…”
Section: Introductionmentioning
confidence: 99%